Ritual Dynamics of Qur’an Burning - Pauha, Teemu (Temenos - Nordic Journal for the Study of Religion, 2024)
In this article I approach Qur’an burning from the perspective of ritual studies. By conducting a discourse analysis of a YouTube video of a Qur’an burning, I argue that it can be perceived as a ritualized performance that communicates a variety of meanings to a variety of audiences. On one hand, the burning demarcates between ‘us’ and a Muslim ‘them’, thus serving to construct an ingroup identity. On the other, Muslims are constructed as a barbaric threat against which a civilized man is justified to use violence. To consolidate intergroup boundaries most effectively, Qur’an burning must be conducted within a community or preferably broadcast to a wide audience. Even when broadcast online, however, the act needs to involve a physical book. Consequently, both online and offline aspects are important for the ritualization of Qur’an burning.